The Integration of Moral Values According to Hashim Asy'Ari Using "Mihya Arabiy" Neuroscience-Assessment Media - Qomariyah, Lailatul; Abdul Qodir; Mu’at; Mz, Isniyatun Niswah; Indana Lazulfa; Iva Inayatul Ilahiyah; Ahya’, Akhmad Sauqi (Asalibuna, 2025)
The decline in students' character values ​​negatively impacts deviant behavior, such as easily believing false news and their inability to compete in society due to their constant dependence on others. This indicates that the achievement of national education goals as stated in Pancasila is still  not optimal. K.H. Hasyim Asy'ari has also initiated his ideas written in the Book of Adabul Alim Wal Mutaallim on how to integrate character values in education, one of which is through the Neuroscience-based evaluation media "Mihya Arabiy". Based on this background, this article focuses on examining the form of integration of Character Values based on the thoughts of K.H. Hasyim Asy'ari in the Mihya Arabiy evaluation media. A qualitative approach and a case study type were used in this study. Data were collected using the Observation method of Arabic language learning in Class VII MTS and analyzed using an interactive model pioneered by Miles and Huberman. The results of this study indicate that the Integration of character values based on the thoughts of K.H. Hasyim Asy'ari in the Neuroscience-based evaluation media Mihya Arabiy is shown with four characters: independence, accuracy, critical thinking, and creative thinking. These four characters are contained in the Neuroscience-based Evaluation media, which has a positive impact on interactive learning, language skills, and improving students' moral value.   ويؤثر تراجع القيم الأخلاقية لدى الطلاب سلبًا على سلوكياتهم المنحرفة، مثل سهولة تصديق الأخبار الكاذبة، وعجزهم عن المنافسة في المجتمع نتيجة اعتمادهم الدائم على الآخرين. وهذا يدل على أن تحقيق أهداف التعليم الوطني، كما وردت في بانكاسيلا، لا يزال دون المستوى الأمثل. كما طرح الحاج الشيخ هاشم أشعرى أفكاره المكتوبة في كتاب "أداب العالم والمتعلم" حول كيفية دمج قيم الشخصية في عملية التعليم، ومن بينها من خلال وسيلة التقييم القائمة على علم الأعصاب "مهيا عربي. وبناء على هذه الخلفية، تركز هذه المقالة على دراسة صيغة اندماح القيم الأخلاقية استناداً إلى أفكار الحاج الشيخ هاشم أشعرى في وسائل التقييم "مهيا عربي". وتعتمد هذه الدراسة على منهج نوعي ودراسة حالة. وجُمعت البيانات باستخدام أسلوب الملاحظة لتعليم اللغة العربية في الصف السابع من المرحلة المتوسطة ومقابلة مع معلم والطلاب فيه، وحُللت البانات باستخدام نموذج تفاعلي ابتكره مايلز وهوبرمان. وتشير نتائج هذه الدراسة إلى أن اندماج قيم الأخلاقية، بناءً على أفكار الحاج الشيخ هاشم أشعرى، في برنامج التقييم  العصبي "مهيا عربي"، يتجلى في أربع سمات: الاستقلالية، والدقة، والتفكير النقدي، والتفكير الإبداعي. وتتجلى هذه السمات الأربع في برنامج التقييم القائم على علم الأعصاب، ومما يُسهم إيجابيًا في التعليم التفاعلي، ومهارات اللغة، وتنمية القيم الأخلاقية لدى الطلاب.